Absolute Capitalism - Bellamy Foster, John (Revista Internacional de Salarios Dignos, 2020)
The French poet Charles Baudelaire wrote in 1864 that “the cleverest ruse of the Devil is to persuade you he does not exist!” I will argue here that this is directly applicable to today’s neoliberals, whose devil’s ruse is to pretend they do not exist. Although neoliberalism is widely recognised as the central political-ideological project of twenty-first-century capitalism, it is a term that is seldom uttered by those in power. In 2005, the New York Times went so far as to make neoliberalism’s nonexistence official by running an article entitled “Neoliberalism? It Doesn’t Exist.” Behind this particular devil’s ruse lies a deeply disturbing, even hellish, reality. Neoliberalism can be defined as an integrated ruling-class political-ideological project, associated with the rise of monopoly-finance capital, the principal strategic aim of which is to embed the state in capitalist market relations. Hence, the state’s traditional role in safeguarding social reproduction—if largely on capitalist-class terms—is now reduced solely to one of promoting capitalist reproduction. The goal is nothing less than the creation of an absolute capitalism. All of this serves to heighten the extreme human and ecological destructiveness that characterises our time.